Internet Freedom in Asia: Case of Internet Censorship in China - MONGGILO, ZAINUDDIN MUDA (Universitas Muhammadiyah Yogyakarta, 2016)
Internet can develop the communication and information freedom on society but unfortunately in some nations, especially in Asia, it cannot be fully accessed because of government censorship. This report explains the relationship between the practice of Internet censorship imposed by the Chinese government and the freedom of its citizens (in the internet surfing experience) as the realization of human rights in the freedom of expression and opinion (seek, receive-use, and communicate information) which is traced through the relevant literature study. China is a unique case since the internet censorship regulation contributes to its status as the country with the least internet freedom yet at the same time it is credited as having the most internet users globally. In addition, China known as the communist country that began opening up to globalization and information of technology, but the government’s control over it is still so tight and binding, not only in the press, or the traditional media, but also in new media with the internet censorship. The control over this information may have a clear objective to maintain a climate of information in the community, but on the other hand, such control is tantamount to restricting the right of citizens to make, use, and distribute information, and more fatal as a violation of human rights.Keywords: Internet, ICT, Censorship, China, Asia